"Orangeism, A Great Protestant Crusade": The Nativist Legacy of the Orange Order in the Northeastern Borderlands. Issue 2 (3rd April 2018) - Cline, Tyler
ABSTRACT: The Orange Order was central to Canadian nativism throughout the nineteenth and twentieth centuries. Formed in 1795 by Protestants who feared the specter of Catholic influence and political involvement in Irish society, the Order protected British authority in Ireland. Its advocacy for British loyalism and Protestant hegemony made it attractive to the growing populace in Anglophone British North America following the American Revolution. The chronological focus of this article will be in the 1920s and 1930s, a period of nativist upsurge decades after the violent heyday of the Order documented in works like Scott See's Riots in New Brunswick: Orange Nativism and Social Violence in the 1840s . It will explore the Orange Order's legacy in New Brunswick, demonstrating its longevity as an anti-Catholic organization and its role in fostering the social acceptance of nativist ideology in the Northeastern borderlands long after the violent 1840s. It will present the Order as an ideological advocate for an ethno-religious strain of identity that espoused Anglo-Saxon Protestant hegemony across the Northeast and collaborated with establishment politicians and fellow nativist organizations like the Ku Klux Klan to enforce this hegemonic worldview in New Brunswick.